HUBUNGAN REGULASI DIRI DENGAN MOTIVASI BERPRESTASI PADA MAHASISWA PG PAUD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU ANGKATAN 2014 - Ernawati '; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research is to know whether there is correlation between sefl regulation and achievement in students of early childhood education teacher program faculty of education university of riau year 2014. The population of this research is the students of early childhood education teacher program faculty of education university of riau year 2014 that consists of 83 students, the samples of this research are 63 students. Method of this research is Pearson Product Moment correlation to know the correlation between sefl regulation and achievement in students of early childhood education teacher program faculty of education university of riau year 2014. The technique of collecting data used questioner in Likert scale form. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows Ver. 18. Based on hypothesis there is any significant positive correlation between sefl regulation and achievement in students of early childhood education teacher program faculty of education university of riau year 2014. It could be seen from the result of correlation coefficient that 0,400 and significant level is 0,01<0,05. The level of correlation between self regulation and achievement motivation of students is in the middle category with the rank of determinant coefficient in the amount 16%, it means that self regulation principal affect achievement motivation as much as 16%.Keywords: Self Regulation, Achievement Motivation